Long Noncoding RNA HCG18 Promotes Malignant Phenotypes of Breast Cancer Cells via the HCG18/miR-103a-3p/UBE2O/mTORC1/HIF-1α–Positive Feedback Loop - Liu, Xu; Qiao, Kun; Zhu, Kaiyuan; Li, Xianglan; Zhao, Chunbo; Li, Jiaqi; Feng, Dawei; Fang, Yu; Wang, Peng; Qian, Cheng; Qiao, Wenbo (Frontiers in Cell and Developmental Biology, 2021)
In recent years, an increasing number of studies have reported that long non-coding RNAs (lncRNAs) play crucial roles in breast cancer (BC) progression and metastasis. Another study group of our research centre reported that lncRNA HCG18 was one of the 30 upregulated lncRNAs in BC tissues compared with normal tissues in The Cancer Genome Atlas (TCGA) database. However, the exact biological roles of HCG18 in BC remain unclear. In this study, we demonstrated that HCG18 is significantly upregulated in BC tissues and cells and that BC patients with high HCG18 expression tend to have poor prognosis. In vitro assays indicated that HCG18 promotes BC cell proliferation and invasion and endows BC cells with cancer stemness properties (CSPs). In vivo assays revealed that knocking down HCG18 in the BC cell line MDA-MB-231 markedly decreased tumour growth and lung metastasis in xenograft mouse models. In terms of mechanism, we found that HCG18 positively regulated the expression of BC-related ubiquitin-conjugating enzyme E2O (UBE2O) by sponging miR-103a-3p, and our previous research verified that UBE2O could promote the malignant phenotypes of BC cells through the UBE2O/AMPKα2/mTORC1 axis. Furthermore, as a downstream target of the HCG18/miR-103a-3p/UBE2O/mTORC1 axis, HIF-1α transcriptionally promoted HCG18 expression and then formed a positive feedback loop in BC. Taken together, these results confirm that HCG18 plays an oncogenic role in BC and might serve as a prognostic biomarker and a potential therapeutic target for BC treatment.